Efecto combinado de un fertilizante mineral y un bioestimulante sobre la producción de forraje verde hidropónico - Rodríguez Ibarra, Jesús Xavier (2021)
The main objective of the research was to evaluate the combined effect of a mineral fertilizer and a biostimulant on the production of hydroponic green forage from corn. The treatments tested were soluble mineral compound Fertilizer (T1), Biostimulant (T2), Soluble mineral compound Fertilizer + Biostimulant (T3) and Control treatment (T4). A completely randomized design (DCA) was used with five replicas and 20 experimental units, consisting of five 1 kg capacity germination trays. The variables recorded were plant height (cm), biomass fresh weight (kg), protein, fiber and ash content (%). The results showed that the plant height, the biomass yield and the protein content were significantly (p <0.05) by the tested fertilization treatments, where the soluble mineral compound fertilizer showed an increase in biomass production of 18.61, 12.36 and 9.2 %, in relation to the control treatments, biostimulant and the combination of soluble mineral compound fertilizer + biostimulant, respectively. Similarly, the soluble mineral compound fertilizer showed a higher crude protein content in the forage tissue, with an increase of 26.21, 17.58 and 7.49% in relation to the control treatments, biostimulant and the combination of soluble fertilizer + biostimulant, respectively. Based on the results found, the soluble mineral compound fertilizer could be used in the production of hydroponic green maize forage.